Multiple nanosecond pulsed electric fields stimulation with conductive poly(l‐lactic acid)/carbon nanotubes films maintains the multipotency of mesenchymal stem cells during prolonged in vitro culture. (7th July 2020) - Chen, Jiaqing; Huang, Yiqian; Yang, Jiabei; Li, Kejia; Jiang, Yangzi; Heng, Boon Chin; Cai, Qing; Zhang, Jue; Ge, Zigang
Abstract: Mesenchymal stem cells (MSCs) gradually lose multipotency when cultured for prolonged durations in vitro, which significantly hinders subsequent clinical applications. Nanosecond pulsed electric fields (nsPEFs) have been recently investigated to overcome this problem in our lab; however, the differentiation potency of MSCs could only be partially and transiently recovered because the nsPEFs can only be delivered to suspended cells once. Here, we develop a new strategy to apply multiple nsPEFs to adherent MSCs with conductive films to mitigate the decreasing multipotency of prolonged cultured MSCs. The poly(l ‐lactic acid)/graphitized‐carboxylated functionalized carbon nanotubes (PLLA/CNT) films were fabricated as conductive cell culture platforms. Both single and multiple nsPEFs stimulation could significantly increase the differentiation potential of MSCs, as evidenced by upregulated expression of chondrogenic, osteogenic, and adipogenic‐related gene ( SOX9, RUNX2, and PPAR‐γ ), as well as increased production of proteoglycans, mineralized calcium, and triglycerides. Multiple nsPEFs stimulation demonstrated significant efficacy in upregulating expression of pluripotency genes of OCT4A (3.5‐ to 4.5‐folds), NANOG (3.5‐ to 4.0‐folds), and SOX2 (1.5‐ to 2.0‐folds) and stably maintaining high expression of these genes for nearly 23 days. Notably, nsPEFs stimulation did not significantly shorten telomere length. In conclusion, multiple nsPEFs stimulation could effectively mitigate decreasing multipotency of MSCs during prolonged in vitro culture.